A Generic Multi-Level SVM Scheme Based on Two-Level SVM for n-Level Converters - Chen Wei; Xibo Yuan; Yonglei Zhang; Xiaojie Wu (Energies, 2020)
Multi-level converters are widely used in various industrial applications. Among various space vector modulation (SVM) schemes, the multi-level SVM scheme based on two-level space vector pulse width modulation (SVPWM) is recognised as a simplified multi-level SVM scheme, which can reduce the computation complexity. However, this scheme is still complicated when the number of the voltage levels is large. This paper proposes a modified SVM scheme that can further simplify the multi-level SVM scheme based on two-level SVPWM. The proposed SVM scheme can directly determine the two-level hexagon where the reference voltage vector is located by calculating a simple formula. The whole modulation process can be completed by only three steps. Meanwhile, the proposed method is generic for any n-level converter without adding much calculation, which greatly simplifies the modulation process. Experimental results have been provided, which verify the effectiveness and generality of the proposed SVM scheme for two types of multi-level converters.